Revision der im Deutschen Entomologischen Institut aufbewahrten Typen paläarktischer Ichneumoniden (Hymenoptera: Ichneumonidae). - Oehlke, Joachim (Contributions to Entomology = Beiträge zur Entomologie, 1963)
There are revised the types of palearctic Ichneumon-flies in the collection of the Deutsches Entomologisches Institut. Four species were found to be synonyms. Nomenclatural Acts maculata Hedwig, 1937 (Anilasta), Lectotype tibialis Hedwig, 1938 (Anilastus), Lectotype berolinae Strand, 1918 (Conoblasta), syn. n. of Glypta mandibulator (Thunberg, 1822) areolaris Strand, 1918 (Cremastus), syn. n. of Cremastus geminus (Gravenhorst, 1829) monticola Hedwig, 1938 (Holocremna), Lectotype annulitarsis Hedwig, 1938 (Homocidus), Lectotype brevis Hedwig, 1938 (Homocidus), Lectotype ignalinoensis Strand, 1918 (Hoploryptus), syn. n. of Aritranis fugitivus (Gravenhorst, 1829) differens Hedwig, 1938 (Phygadeuon), Lectotype wiesmanni Sachtleben, 1834 (Phygadeuon), Lectotype leucopygoides Strand, 1920 (Spilocryptus), syn. n. of Pycnocryptus director Thunberg, 1822